Smoking attitudes, self-reported practices, and COPD knowledge among adults aged 20–59 years: Insights from a Japanese sample - Yolanda De Fatima De Oliveira Graca; Liu Yang; Cui Mingyu; Afsari Banu Alpona; Taeko Watanabe; Yuko Sawada; Emiko Tanaka; Tokie Anme (Tobacco Induced Diseases)
Introduction Smoking remains a significant public health issue globally, despite efforts to reduce tobacco use. In Japan, smoking persists, particularly among certain groups.